Digital economy and income inequality in China: challenges and way forward / Youqin Liang, Siew King Ting and Abdul Aziz Lai Mohd Fikri Lai - Liang, Youqin; Siew, King Ting; Mohd Fikri Lai, Abdul Aziz Lai (Universiti Teknologi MARA Cawangan Sarawak, 2024)
Digital economy plays an important role in reducing urban-rural income inequality and promoting common prosperity. In 2022, China's digital economy accounted for more than 41.5% of the gross domestic product (GDP). In China, there is a huge gap between urban and rural income resulting from the digital economy amidst rapid economic development. This paper aims to examine the impacts of the digital economy on the urban-rural income gap in China from different aspects such as characteristics, comparisons, policies, and challenges. Using academic databases, a narrative literature review approach was conducted on the impacts of the digital economy on urban-rural income inequality in China and international countries from 2014 to 2023. These empirical findings reveal that the development of the digital economy could narrow the urban-rural income inequality worldwide. However, these conclusions are mixed and inconsistent. The digital economy development on urban-rural income in China has encountered various challenges, such as the urban-rural gap in digital infrastructure, uneven regional digital economic development, and lack of digital talents. This study advances several recommendations to reduce urban-rural income inequality. These include, among others, improvement of enterprise informatisation and new generation information technologies, development of digital infrastructure, expansion of rural human capital, digital integration of rural industries, and enforcement of digital security.